Settlement of Business Disputes Through Arbitration Clauses at the Indonesian National Arbitration Board - Sapsudin, Asep; Zahrah, Halimah; Rubiyanti, Dora (Dinasti Research, 2025)
A Arbitration is an out-of-court method of resolving business disputes. In Indonesia, BANI (Indonesian National Arbitration Board) oversees the arbitration process and provides standard clauses that must be contained in contracts if arbitration is chosen. This study belongs to normative law by utilizing secondary information from various legal references (main, supporting, additional) processed through systematization and harmonization. The arbitration clause functions as a contract safeguard, ensuring legal certainty by binding the parties to resolve disputes based on an agreement. The Arbitration Clause is an element of the agreement that gives the parties the opportunity to determine legal options and/or locations to resolve business issues and their legal consequences. By including an arbitration clause in the contract, business people are guaranteed a fair and legally protected dispute resolution through BANI. This strengthens contract enforcement and provides a clear framework for handling potential conflicts.